Learning beyond the classroom: evaluating the use of Pinterest in learning and teaching in an introductory anthropology class - Nick Pearce; Sarah Learmonth (Journal of Interactive Media in Education, 2013)
This paper details a case study of using Pinterest as an educational resource in an introductory anthropology course. Its use was evaluated through the data provided by the platform itself and focus groups. This evaluation found that Pinterest was a popular and useful tool for developing curated multimedia resources to support students' learning. The focus group findings suggested that online resources were shared by students across a variety of social networks, including but not limited to Pinterest. These resources were shared and used beyond the classroom, both physically in locations outside, but also with friends and family that were not part of the classroom. The opportunities for developing critical thinking through the use of tools such as Pinterest are explored.